2000
DOI: 10.1002/1522-2683(20000901)21:15<3257::aid-elps3257>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

On-chip chiral and achiral separation of amphetamine and related compounds labeled with 4-fluoro-7-nitrobenzofurazane

Abstract: Amphetamine and analogous compounds have been labeled with 4-fluoro-7-nitrobenzofurazane and analyzed on a microfabricated chip. Separation of norephedrine, ephedrine, cathinone, pseudoephedrine, methcathinone, amphetamine and methamphetamine is demonstrated using micellar electrokinetic capillary chromatography (MEKC) and laser-induced fluorescence (LIF) detection. Chiral separations of individual drugs were studied using neutral and negatively charged cyclodextrins (CDs) with and without the addition of an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…This is especially useful as the limited available separation length is often considered to be a limiting factor for an intended MCE separation. Especially for demanding separations like chiral analysis on microchips [7] it has been reported that the separation length has a significant impact on resolution, therefore folded microchannels have been used to enable chiral separations on chips [42,43]. However, the need to incorporate turns, in order to realize long channels on a compact microchip, adds a geometrical contribution to analyte dispersion [44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…This is especially useful as the limited available separation length is often considered to be a limiting factor for an intended MCE separation. Especially for demanding separations like chiral analysis on microchips [7] it has been reported that the separation length has a significant impact on resolution, therefore folded microchannels have been used to enable chiral separations on chips [42,43]. However, the need to incorporate turns, in order to realize long channels on a compact microchip, adds a geometrical contribution to analyte dispersion [44][45][46].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the use of only HS-γ-CD as the selector with high resolution mass spectrometric detection was successfully applied to chiral analysis of synthetic cathinones in seized drug samples, allowing enantiomers of 3,4-dimethylmethcathinone and 3,4-methylenedioxymethcathinone (3,4-MDMC) to be identified. HS-γ-CD was also applied to chiral separation of methcathinone after labelling with a fluorescence dye 4-fluoro-7-nitrobenzofurazane (NBD-F), achieving baseline separation for this derivative [24]. In addition, combining HS-γ-CD with (+)-(18-crown-6)-2,3,11,12-tetracarboxylic acid ((+)-18-C-6-TCA) improved resolutions of chiral separation of six synthetic cathinones [25].…”
Section: Capillary Electrophoresis (Ce)mentioning
confidence: 99%
“…UV DM-β-CD, SBE-β-CD a 1.9 -3.6 Chiral separation and identification of cathinone, methcathinone, phenalkylamines, cocaine and propoxyphene in forensic exhibits and khat plant materials [21] Cathinone, Methcathinone LIF NBD-F labelling + HS-γ-CD Chiral separation of cathinone, methcathinone and phenalkylamines [24] Methcathinone DAD β-CD Chiral separation and identification of methcathinone and phenalkylamines in clandestine tablets and urine a Separation and/or resolution factor(s) is/are obtained from using this/these chiral selector(s). b Total numbers of synthetic cathinones involved in the studies are shown instead of their identities, please refer to the original articles for their identities.…”
Section: Cathinone Methcathinonementioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] The linear imaging detector enables an observation of the real-time separation process of enantiomeric components. Figure 2 shows the real-time monitoring of the chiral separation of AI, when the injection and separation voltages, indicated in the Experimental section, were applied for 50 and 60 s, respectively.…”
Section: Characteristics Of Ai Enantioseparation In Mcementioning
confidence: 99%
“…21 The chiral separation of several amino acids, amphetamine and its derivatives has been achieved by employing CDEKC. [22][23][24] In these studies, laser-induced fluorescence (LIF) detection was employed, which is the most commonly used detection technique in MCE, due to its high sensitivity. 25,26 In LIF detection, the analytes should be derivatized prior to MCE analysis, because most compounds are not fluorescent, however, this is not possible for all compounds.…”
Section: Introductionmentioning
confidence: 99%